Youssef's syndrome - a need to review our ways - Pranay Kr Phukan; Kiran R. Konda (Barpeta Obstetrics and Gynaecological Society, 2022)
Vesicouterine fistulas are rare gynaecological fistulas. Multiple causative factors are known. A trending cause now a days is the increase in rate of lower segment caesarean section. We present a case of 25 year old primipara who presented with cyclical hematuria, amenorrhea and urinary continence, 7 months after her cesarean section. She was diagnosed with vesicouterine fistula by hysterosalpingography. After cystoscopic confirmation of size and relation to the trigone of bladder, the fistula was excised by transvesical approach via laparotomy.